Kit VisMat.SE Application Innovation : Simple, Attractive And Joyful Mathematics - Aziz, Norhayati Abd; Theng, Leong Theng; Wahab, Mohd Zulkarnain Abdul; Mansor, Alina Mazwin; Nadzeri, Mohamad Basri; Rosdi, Mohamad Affandi (Angstrom Centre of Education, 2024)
The teaching method of Mathematics needs to be changed in order to give understanding and create interest in learning among students. The KIT VisMat.SE innovation is an application to solve the difficulty special education students to understand the concept of digit value and place value as well as writing two-digit numbers correctly. The problem of students not being able to understand the concept of digit value causes students to lose interest in mathematics teaching. The main objective of this innovation is to help autistic and intellectual disability students being under the Learning Difficulties (LD) category to understand the concept of digit value and place value in simple, attractive and joyful way. Based on Cognitive Theory, the researcher bridges the gap between the existing theory and practical practice of teachers and mathematics textbooks which sometimes do not go hand in hand with the theory which contributes to failure in students' understanding of mathematical concepts. The innovation of this application appliying sample images, colors and digital materials. The study involved 10 LD primary students in Johor. Respondents were categorized into three groups which were one conventional group and two experimental group. Group 1 was taught with a conventional approach while group 2 and group 3 were taught using VisMat.SE Module and KIT VisMat.SE. This mixed method explanatory design study aims to investigate the effectiveness of KIT VisMat.SE to help LD to understand number value, place value and digit value. Findings from this study have succeeded in providing an easy and enjoyable understanding of math concepts and eliminating LD students frustration with math.